Bone marrow examination in cases of pancytopenia - Shah, Pinal; Patel, R. D.; Gamit, Bhavna; Gheewala, Shruti (International Journal of Research in Medical Sciences, 2017)
Background: Pancytopenia is a relatively common hematological entity. This study was undertaken to find out the various causes of pancytopenia by bone marrow examination of patients admitted to New civil hospital, Surat, Gujarat, India. Methods: This was a prospective study carried out to identify the causes of pancytopenia based on bone marrow examination. Bone marrow examinations were performed in 144 cases for different indications over a period of one year 2015, out of which 40 cases have fulfilled the criteria of pancytopenia. Results: Total 40 cases of pancytopenia were examined during period of one year. The commonest cause of pancytopenia was megaloblastic anemia (35%) followed by aplastic anemia (32.5%). other cause includes acute leukemia, myelodysplastic syndrome (MDS) and round cell tumor. Conclusions: Bone marrow aspiration coupled with trephine biopsy can diagnosed majority cases of pancytopenia. Megaloblastic anemia and aplastic anemia are the commonest causes of pancytopenia. A comprehensive clinical and hematological study of patients with pancytopenia will help in the identification of underlying cause.